2016
DOI: 10.1016/j.reprotox.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of recent developmental immunotoxicity studies with bisphenol A in the context of the 2015 EFSA t-TDI

Abstract: Summary Humans are exposed to bisphenol A (BPA) mainly through the diet, air, dust, skin contact and water. There are concerns about adverse health effects in humans due to exposure to bisphenol A (BPA). The European Food Safety Authority (EFSA) has extensively reviewed the available literature to establish a temporary Tolerable Daily Intake (t-TDI). This exposure level was based on all available literature published before the end of 2012. Since then, new experimental animal studies have emerged, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 19 publications
2
30
1
1
Order By: Relevance
“…Effects of BPA on innate immune responses were also observed . Prior to CLARITY, an expert panel concluded that there was credible evidence that BPA could induce abnormal immune responses after relatively low levels of exposure (5 μg/kg BW/d) during development …”
Section: Immune End‐pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of BPA on innate immune responses were also observed . Prior to CLARITY, an expert panel concluded that there was credible evidence that BPA could induce abnormal immune responses after relatively low levels of exposure (5 μg/kg BW/d) during development …”
Section: Immune End‐pointsmentioning
confidence: 99%
“…117 Prior to CLARITY, an expert panel concluded that there was credible evidence that BPA could induce abnormal immune responses after relatively low levels of exposure (5 μg/kg BW/d) during development. 118 Within the CLARITY-BPA consortium, the Kaminski laboratory examined immune cell populations residing in the spleen and thymus. 119 Only animals that were continuously exposed to BPA throughout life were utilized in two published studies resulting from this work.…”
Section: Immune End-pointsmentioning
confidence: 99%
“…Along with concerns related to the effects of estrogenic EDCs like BPA on the reproductive system, there is much scientific and public health interest related to answering the question of whether or not BPA influences the function of the immune system 8, 9 . The idea that environmental estrogens alter immune function is founded upon important differences in the inflammatory responses of females and males.…”
Section: Introductionmentioning
confidence: 99%
“…The foundations of the presented studies were based on our previous observations that the estrogenic actions of BPA and EE could induce pathologic fibrosis and inflammatory pathology of the uterus of exposed females 23,24 . Other previous studies have investigated the potential for the endocrine disruptor BPA to disrupt immune function by focusing on determining whether BPA exposure altered various physiologic properties of isolated immune cells, by establishing an association between exposure and inflammatory or autoimmune disease, or whether exposure to BPA modified immune or inflammatory responses in specific animal models 9,10,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The disruptive mechanisms of BPA action are related to estrogen signaling, which in some cases can also result in alterations of thyroid hormone and androgen signaling, and abnormal hormonal control of metabolism [6][7][8] . Along with concerns related to estrogenic EDCs like BPA having direct effects on the reproductive system, there is much scientific and public health interest related to answering the question of whether or not BPA influences the function of the immune system 9,10 . The idea that environmental estrogens alter immune function is founded upon important differences in the inflammatory responses of females and males.…”
Section: Introductionmentioning
confidence: 99%